The innovation of hybrid module system based on literacy in increasing critical thinking activities for millennial learners in the digitalization era - Nur Rahma Putra, Andika Bagus; Nurul Ulfatin, Nurul Ulfatin; Sumarli, Sumarli; Yee, Mei Heong; Poppy Puspitasari, Poppy Puspitasari; Mindart, Erwin Komara; Anita Dwi Rahmawati, Anita Dwi Rahmawati (2023)
The era of digitalization requires millennial students to love reading and critical thinking. However, it was foundthat this was still a relatively very low percentage. This study aims to: (1) map the need for increasing critical thinkingactivities for millennial learners; (2) develop an innovative hybrid system module with a fond of literacy concept; and(3) test the attractiveness and feasibility of hybrid innovation system modules with the concept of fond of literacy. Overall, this study uses the R&D method. In this study, learning application and curriculum experts carriedout theattractiveness and feasibility tests. The results of this study include (1) aspects of needs in increasing millennial students' thinking activities, namely the up-to-date learning environment (94%), increasing problem solving(90%), asking questions (84%), increasing understanding of other people's points of view (88%) ), and think futuristic (90%); (2) the hybrid innovation system module with the concept of fond of literacy which is developed has superior features of virtual training and level quizzes; and (3) hybrid innovation system module with the concept of fond of literacywhich is developed feasible and interesting (the average expert test score is 92)